(untitled) (Scientia Agricola, 2013)
Rooted leafy cuttings of three Greek olive (Olea europaea L.) cultivars (Koroneiki, Kothreiki and Chondrolia Chalkidikis) were grown for six months in three soil types, in an experimental greenhouse, in order to investigate: i) if their root system was colonized by arbuscular mycorrhiza fungus (AMF) genus and, ii) if genotypic differences concerning growth and mineral nutrition of olive plants existed. Gigaspora sp. colonized the root system of the three cultivars studied, while Glomus sp. colonized only the root system of 'Koroneiki'. Furthermore, in most cases root colonization by AMF differed among cultivars and soil types. The maximum root colonization, in all soils, was found in 'Chondrolia Chalkidikis'. In the three soils studied, the ratio shoot dry weight (SDW)/ root dry weight (RDW) was higher in 'Chondrolia Chalkidikis' than in the other two cultivars. Furthermore, root system morphology of the three olive cultivars was completely different, irrespectively of soil type. Leaf Mn, Fe, Zn, Ca, Mg, K and P concentrations, as well as total per plant nutrient content and nutrient use efficiency, differed among cultivars under the same soil conditions. These differences concerning root morphology, SDW/RDW, as well as nutrient uptake and use efficiency, could be possibly ascribed to the differential AMF colonization by Glomus sp. and Gigaspora sp.